Personification and Depersonification Figures of Speech in the Poetry Hati yang Kemarin Tertawa by Theoresia Rumthe and Weslly Johannes - Roito Putra Indah Sihaloho; Petrus Jacob Pattiasina; Martha Maspaitella (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
Figures of speech or language styles represent figurative expressions employed by authors as a creative medium to convey emotional nuances and intrinsic thoughts. This research aims to analyze and describe the implementation of personification and depersonification figures of speech in the poetry Hati yang Kemarin Tertawa by Theoresia Rumthe and Weslly Johannes, which is compiled in the poetry anthology Percakapan Paling Panjang Perihal Pulang Pergi (2021). Adopting a qualitative descriptive methodology, the data collection techniques utilized in this study comprised close reading and systematic note-taking techniques to categorize textual figures of speech. The empirical findings indicate a total of 9 occurrences, consisting of 5 instances of personification figures of speech and 4 instances of depersonification figures of speech. These results demonstrate that Hati yang Kemarin Tertawa serves as an integral poetry in the collaboration of Theoresia Rumthe & Weslly Johannes that quite intensively incorporates both personification and depersonification devices to establish vivid poetic imagery and emotional depth. Consequently, this study contributes valuable stylistic insights into the rhetorical dynamics of contemporary Indonesian poetry.